2016
DOI: 10.1002/bdd.1995
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling of a novel antithrombotic compound, S002‐333 and enantiomers: metabolic stability, species comparison and in vitro–in vivo extrapolation

Abstract: The in vitro CLint values for S002-333, S004-1032 and S007-1558 were 0.027 ± 0.005, 0.025 ± 0.004 and 0.036 ± 0.005 ml/min/mg, respectively, in PHLM, indicating that S007-1558 was the most metabolically unstable of the three. The LM of other species showed similar results. A common surrogate species to humans for S002-333 and enantiomers was predicted as rabbit where the extrapolated hepatic clearance (CLH ) did not show a significant difference to the in vivo CLH values. However, none of the species closely m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In another study, Saxena et al (102) characterized the metabolism of S002-333 [2-(4'-methoxy-benzenesulfonyl)-2,3,4,9-tetrahydro-1H-pyrido(3,4-b)indole-3-carboxylic acid amide] and its enantiomers, S004-1032 and S007-1558, using liver microsomes from different species. In case of compound S002-333, the highest CL int values were noted in MnLM and were comparable to the values for RLM.…”
Section: In Vitro-in Vivo Extrapolationmentioning
confidence: 99%
“…In another study, Saxena et al (102) characterized the metabolism of S002-333 [2-(4'-methoxy-benzenesulfonyl)-2,3,4,9-tetrahydro-1H-pyrido(3,4-b)indole-3-carboxylic acid amide] and its enantiomers, S004-1032 and S007-1558, using liver microsomes from different species. In case of compound S002-333, the highest CL int values were noted in MnLM and were comparable to the values for RLM.…”
Section: In Vitro-in Vivo Extrapolationmentioning
confidence: 99%
“…In‐vitro CL int of S009–0629 at 5 and 10 µM was calculated as 5.10 ± 0.46 and 4.94 ± 0.47 µL/min/mg, respectively. Scaled in‐vitro CL int in rat liver microsomes was calculated using the values of liver weight of 10 g, rat body weight of 250 g and MPPGL of 45 mg/kg (Saxena et al, ). Scaled in‐vitro CL int of S009–0629 at 5 and 10 µM was calculated as 9.18 ± 0.82 and 8.90 ± 0.84 mL/min/kg of bw.…”
Section: Resultsmentioning
confidence: 99%
“…The in‐vitro half‐life ( t 1/2 ) was calculated as 0.693/K. The in‐vitro intrinsic clearance (in‐vitro CL int ) was calculated using the Equation (Marques et al, ; Saxena et al, ). normalInormaln normalvnormalinormaltnormalrnormalo normalCnormalLnormalinormalnnormalt=0.693t1/2×normalVnormalonormallnormalunormalmnormale normalonormalf normalrnormalenormalanormalcnormaltnormalinormalonormaln normalmnormalinormalxnormaltnormalunormalrnormale true(normalmnormalLtrue)normalmnormalg normalonormalf normalpnormalrnormalonormaltnormalenormalinormaln normalrnormalenormalanormalcnormaltnormalinormalonormaln …”
Section: Methodsmentioning
confidence: 99%
“…With these approaches still under investigation, we took an initiative to develop a clinically useful synthetic molecule targeting platelet–collagen interaction at the sites of arterial injury or plaques. This compound 6b (CDRI-S002-333) is undergoing pharmacokinetic and toxicological studies. From the pharmacokinetic studies it was observed that the isomer 6c or 6d does not interconvert in vivo.…”
Section: Discussionmentioning
confidence: 99%